Financial Market Development and CO2 Emissions Nexus in Nigeria: An Application of ARDL Approach - Musa, Kabiru Saidu; Chindo, Sulaiman; Maijama'a, Rabiu (Journal of Developing Economies, 2021)
The paper investigated the impact of financial development on CO2 emissions in Nigeria from 1981 to 2019. In the process of investigating the impact, Augmented Dickey-Fuller and Philip Perron, as well as the Zivot-Andrew structural breaks, unit root tests were applied. Their results indicated that financial development, level of income, and CO2 emissions were stationary at the first difference and that of Zivot-Andrew structural breaks indicated a mixture of integration. Cointegration relationship among the variables was established through autoregressive distributed lag model bounds test. The autoregressive distributed lag model long-and-short run models results indicated that financial development and income level significantly negatively impact the CO2 emissions. The suggestion based on these results is that financial development and income level help in financing clean projects in the long-and-short runs. The Granger causality result revealed bidirectional causality from financial development to CO2 emissions, income level to CO2 emissions, and financial development to income level. The variance decomposition analysis indicates that financial development and income level have contributed less to CO2 emissions, and impulse response function results revealed that CO2 emissions respond negatively to shocks in financial development and income level. Therefore, we recommend expanding the Nigerian financial market in financing clean projects for a clean environment alongside checking income generation activities that bring about emissions of CO2, such as burning trees for charcoal production in the forest, among others. Keywords: Financial Market Development, CO2 Emissions, ARDL Approach JEL: G20, Q53, C32